2020
DOI: 10.1002/chem.202001551
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Assisted Hydrogen Bonding Phenomenon Unveiled through Both Experiments and Theory: A New Family of Ethyl N‐Salicylideneglycinate Dyes

Abstract: Extensive experimental and theoretical investigations are reported on the nature of resonance-assisted hydrogen bonding phenomenon (RAHB) and its influenceo n photophysical properties of the newly designed dyes differing in donor-acceptor properties, namely ethyl N-salicylideneglycinate (1), ethyl N-(5-methoxysalicylidene)glycinate (2), ethyl N-(5-bromosalicylidene)glycinate (3)a nd ethyl N-(5-nitrosalicylidene)glycinate(4). All compounds are thermochromic in the solid state and they contain at ypical intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 80 publications
(262 reference statements)
1
19
0
Order By: Relevance
“…Dyes 1 – 4 were produced according to the described synthetic procedure [ 18 ]. We first applied a Hirshfeld surface analysis [ 39 ] to study the intermolecular interactions in the reported crystal structures of 1 – 4 [ 17 ]. As a result, a set of 2D fingerprint plots [ 40 ] were generated using CrystalExplorer 3.1 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dyes 1 – 4 were produced according to the described synthetic procedure [ 18 ]. We first applied a Hirshfeld surface analysis [ 39 ] to study the intermolecular interactions in the reported crystal structures of 1 – 4 [ 17 ]. As a result, a set of 2D fingerprint plots [ 40 ] were generated using CrystalExplorer 3.1 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular surface of 3 is additionally characterized by a remarkable proportion of the H∙∙∙Br intermolecular contacts of 17.4%, with the shortest contacts at d e + d i ≈ 3.0 Å ( Figure S3 ). Notably, the molecular surface of 3 is further described by a distinct proportion of the C∙∙∙C contacts of 4.1%, which is due to intermolecular π⋯π stacking interactions between the phenylene rings [ 17 ]. These contacts are shown on the 2D plot as a typical area at d e = d i ≈ 1.7–2.0 Å ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations